2019
DOI: 10.1002/mma.5501
|View full text |Cite
|
Sign up to set email alerts
|

Blow‐up of solutions for a viscoelastic wave equation with variable exponents

Abstract: In this paper, we consider a viscoelastic wave equation with variable exponents: utt−Δu+∫0tg(t−s)Δu(s)ds+a|utfalse|m(x)−2ut=b|ufalse|p(x)−2u, where the exponents of nonlinearity p(·) and m(·) are given functions and a,b > 0 are constants. For nonincreasing positive function g, we prove the blow‐up result for the solutions with positive initial energy as well as nonpositive initial energy. We extend the previous blow‐up results to a viscoelastic wave equation with variable exponents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In this part, our goal is to prove the local existence result for our main problem (1.1) by using Faedo-Galerkin method. We use similar arguments as in [14,16] to get the result. Firstly, we give the lemma which we need:…”
Section: Local Existencementioning
confidence: 99%
See 1 more Smart Citation
“…In this part, our goal is to prove the local existence result for our main problem (1.1) by using Faedo-Galerkin method. We use similar arguments as in [14,16] to get the result. Firstly, we give the lemma which we need:…”
Section: Local Existencementioning
confidence: 99%
“…In recent years, some other authors investigate hyperbolic type equation with variable exponents (see [8,13,16,18,24]).…”
Section: Introductionmentioning
confidence: 99%
“…See [6,7,11] for more properties of a Lebesgue space with variable exponent. By combining the arguments of [10,19], for every (w 0 , w 1 ) ∈ H 2 0 ( ) × L 2 ( ), we can get a unique local solution w of problem (1.1)-(1.4) with w ∈ C(0, T; H 2 0 ( )) ∩ C 1 (0, T; L 2 ( )) and w t ∈ L 2 (0, T; H 1 0 ( )).…”
Section: Preliminariesmentioning
confidence: 99%
“…Furthermore, they showed that the solution with negative initial energy blows up in a finite time. Later, Park and Kang [19] improved and complemented the result of [15] by obtaining a blow-up result of solution with certain positive initial energy for a wave equation of memory type. We also refer to a recent work [4] for a nonlinear diffusion system involving variable exponents dependent on spatial and time variables and cross-diffusion terms.…”
Section: Introductionmentioning
confidence: 98%
“…They proved a blowup in finite time with negative initial energy under suitable conditions on g, f and the variable exponent of the ⃗ p(x, t)-Laplace operator. For more results regarding this matter, we refer the reader to previous studies [13][14][15][16][17][18] and the review paper. 19 Motivated by the aforementioned works, in the present paper, we study a class of elastic inverse source problem with variable-exponent nonlinearities.…”
Section: Introductionmentioning
confidence: 99%